1967
DOI: 10.2136/sssaj1967.03615995003100040031x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Crop Management on Runoff, Erosion, and Soil Properties of a Marshall Silty Clay Loam

Abstract: A series of field plots at Clarinda, Iowa, were operated from 1932 through 1963 to study effects of crop and soil management on infiltration, erosion, and crop yield. Major treatment changes were made in 1943 and 1953. Before 1953, soil‐erosion rates were high, especially when corn (Zea mays L.) followed several years of corn, and were inversely related to organic carbon content and aggregate stability of the soil.After the 1953 revision of the study, erosion loss from continuous corn that received annual appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

1972
1972
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
6
0
2
Order By: Relevance
“….From preliminary experiments in Illinois, Melsted (1954) concluded that in soils cropped to continuous corn with an ample supply of N the level of organic matter decreased under clean cultivation. Similar results on a Marshall silty clay loam were obtained by Moldenhauer, Wischmeier, and Parker (1967) when the initial C content was 1.84%. When the soill had been severely depleted of organic matter (1.35% C) by continuous cropping of corn without fertilization, however, high N applications for 12 years resulted in an increase of organic C. Short-term studies by Sutherland, Shrader, and Pesek ( 1961) also indicatEd increases in soil organic matter.…”
supporting
confidence: 81%
“….From preliminary experiments in Illinois, Melsted (1954) concluded that in soils cropped to continuous corn with an ample supply of N the level of organic matter decreased under clean cultivation. Similar results on a Marshall silty clay loam were obtained by Moldenhauer, Wischmeier, and Parker (1967) when the initial C content was 1.84%. When the soill had been severely depleted of organic matter (1.35% C) by continuous cropping of corn without fertilization, however, high N applications for 12 years resulted in an increase of organic C. Short-term studies by Sutherland, Shrader, and Pesek ( 1961) also indicatEd increases in soil organic matter.…”
supporting
confidence: 81%
“…(2) 01/01/93 a 08/06/93; (3) 09/06/93 a 17/11/93; (4) 18/11/93 a 12/07/94; (5) 13/07/94 a 18/11/94; (6) 19/11/94 a 30/07/94; (7) 01/08/95 a 30/11/95; (8) direta, respectivamente, em relação à sucessão de culturas, na média do período de estudo (Quadro 4), concordando com dados obtidos por Lombardi Neto (1994). Este comportamento pode ser explicado pela alternância das culturas e práticas culturais na rotação, com conseqüente manutenção de cobertura vegetal variada e uniforme e elevado conteúdo de matéria orgânica, refletindo-se nas propriedades físicas do solo e, geralmente, na erosão (Uhland, 1949;Moldenhauer et al, 1967;.…”
Section: Sistemaunclassified
“…A rotação de culturas, caracterizada por um sistema de cultivo baseado na alternância de espécies vegetais, planejada e recorrente no tempo e no espaço, melhora, em geral, as condições físicas e químicas do solo, as quais concorrem para a redução da erosão hídrica (Uhland, 1949;Moldenhauer et al, 1967;.…”
Section: Introductionunclassified
“…Green manure crops are forages that get plowed into the soil at the end of the growing season to improve lts structure and stability against erosion. In a ten year study, Moldenhauer et al (1967) obtained reductions in soil loss and runoff of 30% and 37% respectively for a 3 year rotation of oats, corn and alfalfa-brome hayon a silty clay loam soil.…”
Section: 412croppinq Systemsmentioning
confidence: 99%